Red Ginseng Inhibits Tau Aggregation and Promotes Tau Dissociation In Vitro. (1st July 2020) - Shin, Soo Jung; Park, Yong Ho; Jeon, Seong Gak; Kim, Sujin; Nam, Yunkwon; Oh, Sang-Muk; Lee, Yong Yook; Moon, Minho
Abstract : Tau, a microtubule-associated protein expressed in mature neurons, interacts with tubulin to promote the assembly and stabilization of microtubules. However, abnormally hyperphosphorylated tau dissociates from microtubules and self-aggregates. Tau aggregates, including paired helical filaments and neurofibrillary tangles, promote neuronal dysfunction and death and are the defining neuropathological feature of tauopathies. Therefore, suppressing tau aggregation or stimulating the dissociation of tau aggregates has been proposed as an effective strategy for treating neurodegenerative diseases associated with tau pathology such as Alzheimer's disease (AD) and frontotemporal dementia. Interestingly, ginsenosides extracted from Panax ginseng reduced the hippocampal and cortical expression of phosphorylated tau in a rat model of AD. However, no studies have been conducted into the effect of red ginseng (RG) and its components on tau pathology. Here, we evaluated the effect of Korean red ginseng extract (KRGE) and its components on the aggregation and disassociation of tau. Using the thioflavin T assay, we monitored the change in fluorescence produced by the aggregation or disassociation of tau K18, an aggregation-prone fragment of tau441 containing the microtubule-binding domain. Our analysis revealed that KRGE not only inhibited tau aggregation but also promoted the dissociation of tau aggregates. In addition, the KRGE fractions, such as saponin, nonsaponin, and nonsaponin fraction with rich polysaccharide, also inhibited tau aggregation and promoted the dissociation of tau aggregates. Our observations suggest that RG could be a potential therapeutic agent for the treatment of neurodegenerative diseases associated with tauopathy.